Risiko Ide Bunuh Diri Siswa SMA, Seberapa Tinggi? - Roziqi, Masbahur; Kusmiati, Kusmiati; Afandi, Achmad Jasuli (Jurnal Psikoedukasi dan Konseling, 2025)
The trend of suicide among adolescents is on the rise, especially among high school students. Suicide risk factors in adolescents are the cause of suicidal ideation in these adolescents. This research employs a survey research design. The study population consists of 607 students. Data collection utilizes the adoption of an early detection scale for suicide risk factors in high school adolescents. The analysis technique used is descriptive analysis. The research findings show that (1) 56 percent of students have low-risk factors, 42.5 percent have moderate risk factors, and 1.5 percent have high-risk factors for adolescents suicidal ideation; (2) Burdensomeness and loneliness have the highest percentages in terms of the dimensions of suicide risk factors; (3) Female high school students are at a higher risk of having suicidal ideation compared to male high school students; (4) The 10th-grade adolescents students are at a higher risk of having suicidal ideation than 11th-grade adolescents students. It can be concluded that suicide risk factors in adolescents are crucial for the government, schools, and society to be aware of. Further research recommendations include the development of basic and responsive intervention services to reduce suicide risk factors in high school adolescents.